Learning and teaching geological field skills in a virtual world:insights from an undergraduate virtual fieldtrip in Kinlochleven, Scotland - Genge,M; Laurent,V; Mason,P; Spencer,A; Sutton,M; Whittaker,A (Earth Science, Systems and Society, 2024)
Virtual fieldtrips enable the teaching of field geology remotely or in classroom-settings by leveraging video-game technologies. Wedescribe the development of a virtual fieldtrip to Kinlochleven in Scotland to teach undergraduate students geological mapping skillsin a structurally complex, polyphase deformed metamorphic terrain. An area of ~4 km 2 of the Highlands was digitally replicatedwithin the game engine Unity and featured 82 outcrops digitized from field data by photogrammetry. Key concepts in thedevelopment were: (1) usability on low-specification computers, (2) participant communication within-app, (3) multiscalevisualisation of localities, (4) contextualisation of localities within terrain, and (5) a high degree of immersion to replicate theoutdoor fieldwork experience. Technology constraints, however, required compromise between the number of localities used andtheir resolution. Evaluation and assessment data suggests the virtual fieldtrip was effective in delivering the key learningobjectives of the course. Student behavioural indicators, furthermore, suggest that the immersive strategy successfully produceda high degree of engagement with the activity. A major limitation of the virtual fieldtrip was in the development of skillsrequiring spatial visualisation, in particular, the spatial association of features across multiple scales. The virtual fieldtrip hadbenefits for inclusivity, making fieldwork more accessible than its outdoor equivalent. However, a digital divide was observed toexist between groups depending on experience with gaming and virtual worlds. In addition, neurodiverse group of studentsrequired adaptations to assist with spatial awareness in virtual environments. The data obtained suggests that virtual fieldtripscannot fully replace their outdoor equivalents, however, they are valuable in supplementing and supporting outdoor fieldtrips, inparticular by increasing inclusivity and enabling field time to be used optimally.